A liberal developmental state in Georgia? State dominance and Washington Consensus in the post-communist region - Christian Timm (PFH Private Hochschule Göttingen, 2014)
The article analyzes state dominance in Georgia's economy between 2003 and 2010 from the perspective of the (new) developmental state. The specific interlinkage of economic model, law and administration through which state interventions may generate market-enhancing effects provides the analytical framework for the examination of Georgia's institutional setting. The article argues that Georgia enjoyed favorable exogenous conditions for the emergence of a developmental state and was about to introduce a set of administrative features similar to developmental states. However, two factors significantly shaped state-economy relations different to developmental states. Firstly, Georgia opted for a radical anti-corruption-driven separation of state and economy and pursued, consequently, a strict Washington Consensus economic policy. In doing so, the government simultaneously abandoned effective formal instruments for the politically relevant steering of the distribution of economic advantages. This in turn increased the necessity for informal interventions in economic processes contradicting the chosen economic model. Secondly, the flexibility-approach of the government, which relied rather on capable managers than on structures and procedures, undermined the administrative reforms and prevented the emergence of an 'embedded autonomy' of the public service. The absence of a capable, institutional learning and autonomous administration must be seen as the major obstacle for the elaboration of appropriate strategies after 2008 when the government altered its neo-liberal approach towards state-managed capitalism. Although the government was able to steer private and public investments in the specific sectors by relying on its informal coercive power, the economic success of this economic policy, however, failed to appear. The article argues that the lack of an independent administration and the renunciation of means of formal coordination and of law in general are to be made responsible for this. In doing so, Georgian policy makers also waived the chance to reconcile their agenda of sustainable economic growth with the agenda of political power preservation. The study seeks to contribute to the question of institutional prerequisites for successful state interventions in Low- and Middle-Income Countries and, hence, to the growing literature on Post-Washington Consensus and New Developmentalism.
Keywords: 330